West German Study Group Phase III PlanB Trial: First Prospective Outcome Data for the 21-Gene Recurrence Score Assay and Concordance of Prognostic Markers by Central and Local Pathology Assessment - Gluz, Oleg; Nitz, Ulrike A.; Christgen, Matthias; Kates, Ronald E.; Shak, Steven; Clemens, Michael; Kraemer, Stefan; Aktas, Bahriye; Kuemmel, Sherko; Reimer, Toralf; Kusche, Manfred; Heyl, Volker; et al. (Journal of clinical oncology, 2016)
The 21-gene Recurrence Score (RS) assay is a validated prognostic/predictive tool in early hormone receptor-positive breast cancer (BC); however, only a few prospective outcome results have been available so far. In the phase III PlanB trial, RS was prospectively used to define a subset of patients who received only endocrine therapy. We present 3-year outcome data and concordance analysis (among biomarkers/RS). Central tumor bank was established prospectively from PlanB (intermediate and high-risk, locally human epidermal growth factor receptor 2-negative BC). After an early amendment, HR-positive, pN0-1 patients with RS ≤ 11 were recommended to omit chemotherapy. From 2009 to 2011, PlanB enrolled 3,198 patients with a median age of 56 years; 41.1% had node-positive and 32.5% grade 3 disease. In 348 patients (15.3%), chemotherapy was omitted based on RS ≤ 11. After 35 months median follow-up, 3-year disease-free survival in patients with RS ≤ 11 and endocrine therapy alone was 98% versus 92% and 98% in RS > 25 and RS 12 to 25 in chemotherapy-treated patients, respectively. Nodal status, central and local grade, the Ki-67 protein encoded by the MKI67 gene, estrogen receptor, progesterone receptor, tumor size, and RS were univariate prognostic factors for disease-free survival; only nodal status, both central and local grade, and RS were independent multivariate factors. Histologic grade was discordant between central and local laboratories in 44%. RS was positively but moderately correlated with the Ki-67 protein encoded by the MKI67 gene and grade and negatively correlated with progesterone receptor and estrogen receptor. In this prospective trial, patients with enhanced clinical risk and omitted chemotherapy on the basis of RS ≤ 11 had excellent 3-year survival. The substantial discordance observed between traditional prognostic markers and RS emphasizes the need for standardized assessment and supports the potential integration of standardized, well-validated genomic assays such as RS with clinicopathologic prognostic factors for chemotherapy indication in early hormone receptor-positive BC.